Pengaruh kepuasan kerja terhadap motivasi karyawan - KAREL TJAHJADI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The research objective was to obtain empirical evidence of the factors that affect motivation. These factors are the results of Employment, Wages, Opportunity for Advance-ment, Trust and Responsibility and Working Conditions and Environment. Data collection using questionnaire survey. Research ideal determine factors that motivate employees to work. The sample in this research is as many as 65 employees of XYZ randomly selected will be given a questionnaire about the influence of motivational factors. The results showed that (1) there is a relationship between the results of work and motivation, (2) there was no correlation between salary Received and motivation, (3) there is no relationship between the Opportunity for Advancement and motivation, (4) there is a relationship between the Trust and Responsibility responsibility and motivation, (5) there is no relationship between the Working Conditions and Environment and Motivation.